2021
DOI: 10.5502/ijw.v11i4.1465
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of online, school-based Positive Psychology Interventions to improve mental health and wellbeing: A systematic review

Abstract: Online positive psychology interventions provide a more equitable method for young people to access wellbeing education at school than more traditional face to face programs. This systematic review aimed to examine the effectiveness of universal, online, school-based, positive psychology interventions using recommendations by the Preferred Reporting Items for Systematic reviews and Meta-analyses - protocols (PRISMA-P). Nine articles were identified for the review and were deductively, thematically analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…There is no need for an outside expert to develop a curriculum for the programmes studied above, according to the PPIs analysed. This information supports the argument that teachers should get training in positive education (44). If future PPI tests incorporate teacher reports as well as student reports, qualified instructors will be familiar with the positive psychology evaluation indices, which would be advantageous for future PPI evaluations (58).…”
Section: Creating a Positive School Environmentsupporting
confidence: 61%
See 1 more Smart Citation
“…There is no need for an outside expert to develop a curriculum for the programmes studied above, according to the PPIs analysed. This information supports the argument that teachers should get training in positive education (44). If future PPI tests incorporate teacher reports as well as student reports, qualified instructors will be familiar with the positive psychology evaluation indices, which would be advantageous for future PPI evaluations (58).…”
Section: Creating a Positive School Environmentsupporting
confidence: 61%
“…A practise of paying attention, typically to a single item designated as the centre of concentration is one recognised strategy that has been proven to induce the good sensation of tranquilly. Studies on adults have shown that meditation increases feelings of calm, compassion, reduces stress, enhances physical health, promotes self-compassion, increases selfawareness, and encourages self-regulatory behaviour (44). Meditation should thus be employed in schools to improve well-being of students.…”
Section: Serenity-focussed Positive Psychology Intervention In Schoolsmentioning
confidence: 99%
“…The negatively associated variables in the Self domain were mainly related to mental illness, and universities often provide psychological services to students. But given the finite capacity of university counselling services, and the known rates of mental illness among people in this age group, scalable methods of treatment might be considered [157,158]. Further, despite recent advances, much mental illness still goes untreated, so awareness campaigns and screening programmes might help to bridge this gap.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…There are numerous demonstrations of the efficacy of positive psychology interventions for students' well-being in schools. These are illustrated by systematic reviews which report quantitative analyses of the pooled effect size (Cilar et al, 2020;Francis et al, 2021;Mendes de Oliveira et al, 2022;Tejada-Gallardo et al, 2020). Positive education has had fewer inroads in the higher education setting.…”
Section: Introductionmentioning
confidence: 99%